THE GROWTH AND YIELD OF PADDY CIHERANG PLANTED IN DRY AND RAINY SEASON AND FERTILLIZED WITH ORGANIC AND INORGANIC FERTILIZERS - Santosa, Mudji; Suryanto, Agus (AGRIVITA, Journal of Agricultural Science, 2015)
The study in order to know the growth and yield  of paddy Ciherang planted in dry and rainy season and applicated with organic and inorganic fertilizers  was conducted in paddy soil at  Ngujung . Batu . East Java, with the height areas  is  900 m above sea level , the average of temperatureis  is  220 C and  a soil type is  Andosol . This study is conducted at June up  to October 2013 ( dry season) and February up to May 2014 ( rainy season) and uses a Randomized CompleteBlock Design for  arranging the treatments of fertilizers i.e. : ( a) 100 kgs  N / ha, 50 kgs P2O5 / ha  and 70 kgs  K2O/ha . ( b ) 50 kgs N /ha ,  25 kgs P2O5 /ha  and 35 kgs K2O/ha  ; ( c ) Cow manure 20 tons /ha ;and (d ) Cow manure 10 tons/ha . The field experiment was repeated 3 ( three ) times . The growth and yield of paddy Ciherang planted in dry season higher than planted in wet. Plant height of paddy Ciherang in dry season (years of 2013) is  86.9 cm tall , Leaf Area Index is  4.18 ,  time of harvesting 125 dap,  grains per panicle is 134.2 , 1000 grains weight is 26.1 g and the grains yield  is  984.2 g/m2 (9,84 tons/ha). The same characterstics  of paddy  Ciherang which measured in rainy season (years of 2014) are 87.7 cm tall , LAI  3.70,  time of harvesting 105 dap,  the number of tillers per hill 14.2,  grains per panicle  90.0 , 1000 grains weight  25.8 g and the grains yield 481,8 g/m2 (4,81 tons/ha). Key words : Fertilizers of organic and inorganic ,  rice Ciherang and   the cow manure